2021
DOI: 10.3390/su131910762
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on College Students: An Online Survey

Abstract: The COVID-19 pandemic, since its beginning in December 2019, has altered every aspect of human life. In Vietnam, the pandemic is in its fourth peak and is the most serious so far, putting Vietnam in the list of top 30 countries with the highest daily cases. In this paper, we wish to identify the magnitude of its impact on college students in Vietnam. As far as we’re concerned, college students belong to the most affected groups in the population, especially in big cities that have been hitting hard by the viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
(39 reference statements)
0
21
0
Order By: Relevance
“…Students were able to ask questions via email or attend virtual office hours, but many missed the ease of raising a hand and getting a question answered in real time. According to a study conducted in Vietnam (Tran, et al, 2021), students had generally negative feelings toward online education, with 63.31% of respondents stating that they disliked online exams and 64.8 percent stating that online learning was only marginally effective and only a temporary solution. The difficulties in assessing and testing online, as well as not understanding the course and communicating with peers, were identified as negatives.…”
Section: Discussionmentioning
confidence: 99%
“…Students were able to ask questions via email or attend virtual office hours, but many missed the ease of raising a hand and getting a question answered in real time. According to a study conducted in Vietnam (Tran, et al, 2021), students had generally negative feelings toward online education, with 63.31% of respondents stating that they disliked online exams and 64.8 percent stating that online learning was only marginally effective and only a temporary solution. The difficulties in assessing and testing online, as well as not understanding the course and communicating with peers, were identified as negatives.…”
Section: Discussionmentioning
confidence: 99%
“…As some participants expressed, stress factor during the pandemic has motivated some students to take the easy way out. Studies from Bangladesh (Khan, et al 2021), Hong Kong (Mok, et al 2021), and Vietnam (Tran, et al 2021) also found that students mentally and psychologically struggled during the pandemic, and some showed signs of depression; they did not find online learning satisfying; they lacked the computer skills and sometimes the equipment to complete online assignments.…”
Section: Discussionmentioning
confidence: 99%
“…It is a process of experiencing the sensations and viewpoints of people. Recently Tran et al [16] conducted a student survey to analyze COVID-19 impact on their mental health.…”
Section: Related Literaturementioning
confidence: 99%